THE ROLE OF PUBLIC RELATIONS AND PEACE BUILDING ON SOCIO-ECONOMIC DEVELOPMENT OF SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study aimed at providing a broader understanding of how Public relations and peace building affect Social-economic development of South Sudan. The objectives of the study were to examine the relationship between Public relations and Socio-economic development; analyses the relationship between Peace building and Socio-economic development and to study the factor structure of Public relations and Peace building on Socio-economic development. The study employed a case study and descriptive design while using qualitative and quantitative approaches. The study population was 243, selected using purposive and simple random sampling technique. The sample size determination was made using Krejcie and Morgan Table (1970) formula. The sample size was 167 with a response rate of 85%. The data analysis was made using Statistical package for social scientists (SPSS 20). The major findings of the study were that there was a positive relationship between; public relations and Socio-economic development (r = 0.633, P-value < 0.01; Peace building and Socio-economic development (r = 0.556, P-value < 0.01) and a regression figure of (R= 0.643) a combination of public relations and peace building in assessing the level to which they can predict the level of Socio-economic development of South Sudan. The most influential predictor was public relations with (β = .641, Sig. 325) followed by Institutional response with (β = .443, Sig. 211). The study recommends that the leaders should develop public relations with other international communities that aim at empowering people with education values and promoting an electoral process that serves the purpose of national renewal and peace commitment, organizations and stakeholders should invest heavily in educating their staff and sensitizing their beneficiaries about the need for peace building and where need be, alternative dispute resolution mechanisms such as negotiation, fact finding facilitation and mediation should be adopted and for lobbying be done for more organizations to join in and engage in the peace building process in order to fully curb the issue of armed conflicts and also improve the rate at which peace building is being attained.